Original articleTranscription factor Pax6 is expressed by astroglia after transient brain ischemia in the rat model - Steliga, Aleksandra; Waśkow, Monika; Karwacki, Zbigniew; Wójcik, Sławomir; Lietzau, Grażyna; Klejbor, Ilona; Kowiański, Przemysław (Folia Neuropathologica, 2013)
Reactive astrogliosis is regarded as an universal astrocytic response to different kinds of lesions, concerned with glial fibrillary acidic protein (GFAP) up-regulation, cellular hypertrophy and proliferation. The origin of reactive and proliferating cells in the adult brain is still disputable. Persistent progenitors as well as de-differentiating adult cells of various glial lineages are regarded as possible candidates. Pax6 transcription factor is one of the characteristic markers of astroglial de-differentiation, also important for regulation of neural and glial proliferation. Various kinds of pathological stimuli evoke reactive response, differentiated in its morphological, biochemical and immunological character. The aim of this study was to assess the dynamics of astroglial morphological and proliferative response to ischemic injury. One-hour transient focal cerebral ischemia was applied to evoke the reactive astrogliosis in twenty five adult male Wistar rats. The astrocytic morphological and proliferative reactions to ischemia were studied in the period of 6 weeks by means of GFAP and Pax6 immunofluorescent staining. A strong reactive astroglial response was observed in the cerebral cortex and striatum, manifested by GFAP and Pax6 up-regulation and astrocytic hypertrophy. Apparent morphological changes appeared within 24 hrs after ischemia. The GFAP/Pax6 colocalization was numerous and observed 24 hrs after ischemia. A characteristic spatial distribution of GFAP/Pax6 double-labelled astrocytes and Pax6 single-labelled nuclei was revealed, with the latter situated more distantly from the ischemic core. The maximal intensity of astrocytic reaction was present from the first post-ischemic week. Astroglial hypertrophic changes and proliferative reaction were more intense in the striatum than in the cerebral cortex. Our observations reveal intensive astroglial de-differentiation and proliferative response, reflected by dynamic Pax6 up-regulation within GFAP-immunoreactive astrocytes. Transient cerebral ischemia evokes strong reactive astrogliosis, which is apparently differentiated in respect to the post-ischemic period and particular brain structure.